A case of pancreas divisum associated with pancreatobiliary mal-union - TSUJITA, Shigenobu; KIKUCHI, Eiryou; HOKAZE, Youichi; UMEMOTO, Norie; MORIMURA, Masafumi; NAKATANI, Toshiya; FUKUI, Hiroshi; TSUJII, Tadasu; MATUMOTO, Masami; NAKAYAMA, Masaki (Tando, 1994)
A 27-year-female was admitted to our hospital because abdominal US showed dilatation of common bile duct. ERCP revealed dilatated common bile duct that was connected to the main pancreatic duct at 2.5 cm distal portion from the orfice of papilla Vater. Because the main pancreatic duct was short and smooth in pancreaticography from papilla Vater, pancreaticography from accessory papilla was done. This study disclosed that dorsal pancreatic duct had no connection with ventral pancreatic duct, and a diagnosis of pancreas divisum associated with pancreatobiliary mal-union was made. Co-existence of both anomalies has been rarely reported. We conclude that a care should be paid for the association of pancreas divisum in a case with pancreatobiliary mal-union.